PENINGKATAN KESEHATAN MASYARAKAT MELALUI PEMERIKSAAN KREATININ SEBAGAI DETEKSI DINI PENYAKIT GINJAL DI KELURAHAN TAMALABBA - Rafika Rafika; Zulfikar Ali Hasan; Nurlia Naim (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
The kidney has functions to regulate the secretion of metabolic waste (removing metabolic waste, namely urea, creatinine uric acid and foreign chemicals) useful for the body. People who are at risk of chronic kidney failure, namely over 35 years of age, family history of chronic kidney failure, history of DM, high blood preassure, history of UTIs, smokers, taking supplement drugs in the long term, history of alcohol consumption. The activity method is in the form of community creatinine examination services in Tamalabba village. The location of the posyandu room RW 2 activity in Tamalabba village, Makassar city. This activity was attended by 49 participants including 40 (81.6%) women and 9 (18.4%) men. Creatinine examination through blood samples in community service participants had normal results of 69.4% and abnormal results of 30.6%. Participants in the category of abnormal results, indicating the presence of impaired renal function. The results of the examination are submitted at the puskesmas for follow-up so that participants who carry out other supporting examinations in the puskesmas laboratory.